What's love got to do with it? [videorecording (DVD)] - Sawhney, Nitin, 1964- (Shout! Factory, 2023)
How do you find lasting love in today's world? For documentary-maker and dating app addict Zoe, swiping right has only delivered an endless stream of Mr. Wrongs, to her eccentric mother Cath's dismay. For Zoe's childhood friend and neighbor Kaz, the answer is to follow his parents' example and opt for an arranged (or "assisted") marriage to a bright and beautiful bride from Pakistan. As Zoe films his hopeful journey from London to Lahore to marry a stranger, chosen by his parents, she begins to wonder if she might have something to learn from a profoundly different approach to finding love.